Some Notes and Critiques of Selected Lexicographic Texts in Bikol - Zubiri, Louward Allen (Social Science Diliman: A Philippine Journal of Society and Change; Vol 10 No 2 (2014), 2014)
This study revolves around notes and critiques of Bikol lexicography. Based on a selection of six dictionaries, the structure and diachronic development of Bikol lexicography were analyzed. Half of the selected dictionaries were authored in full or part by Malcolm Mintz, a renowned Bikol expert. These enabled a linear analysis of changes in lexicography that have occurred within the span of four decades. The dictionaries studied include the earliest and most influential Bikol dictionary of Lisboa (1865). The study presents a preliminary description of lexicographic work done in Bikol and traces the shift in the paradigm of dictionary making from the Spanish era to the present. Keywords: Bikol languages, lexicography, diachronic